PENGEMBANGAN MEDIA PEMBELAJARAN POP UP BOOK PADA KETERAMPILAN BERBICARA SISWA KELAS III DI SD NEGERI TANGERANG 2 - Vika Zahra Aini; Erdhita Oktrifianty; Dilla Fadhillah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The purpose of this development research is to develop teaching media in the form of Pop Up Book on Speaking Skills of Third Grade Students at Tangerang 2 State Elementary School using the ADDIE model and method. This research uses observation instruments, interviews, documentation, questionnaires and tests (pre-test & post-test). The results of validation from media experts get a score of 4.4 with a validity level of 87% which is classified as “Worthy (Valid)”. While the results of validation from material experts obtained a score of 4.3 with a validity level of 86% which is classified as “Eligible (Valid)”. Then the validation results from the assessment of the class teacher get a score of 95% which is classified as “Very Feasible”. The results of the student response questionnaire assessment in the small (5 students) and medium (10 students) scale trials received a scoring average of 4.46 with an average feasibility value of 89% which is classified as “Very Good / Very Feasible”. Then the results of the student Post-Test on small and medium scale trials are said to have increased above the minimum achievement target of 80%, which can be categorized as “very good”. Thus it can be concluded that the product developed in the form of Pop Up Book media is very feasible to be used in learning activities in the speaking skills of third grade students at Tangerang 2 State Elementary School. Keywords: speaking skills, pop up book, elementary education